Penerapan Metode Logika Fuzzy Untuk Perlindungan Sistem Tenaga Listrik - Rofi Hariadi; Azriyenni Azhari Zakri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The fault occurs in electric power systems is a critical problem that can affect system reliability. In this study, the protection of power system using the Fuzzy Relation (FR method). The FR method is designed to implement Artificial Intelligent (AI) to predict the work of protective equipment in electrical power systems, namely, state relay status and Circuit Breaker (CB) utilizing the sequence of protective equipment operating time. The logic operating time of this protective device is built on the sagittal diagram. Furthermore, there is a three-dimensional matrix also used to represent the circuit topology in the protection system. Operating time of the protective devices utilizes by the power circuit topology matrix that will be generated every CB status when operating. The test data for the system model have been run on five bus systems in Riau, which is conducted with five fault scenarios. Simulation results found are the fault of each line L1 and L2 with membership degrees of values 0.9419 and 0.9310. The application of the FR method is very suitable to be given a prediction in the protection of the electric power system because it can anticipate more faster the fault that occurs in the electric power system.Keywords: circuit breaker, Fuzzy Relation, protection system, relay, sagittal diagram